Case report: Durable response to alectinib in ALK-rearranged lung adenocarcinoma with acquired, crizotinib-resistant ALK C1156F mutation - Rao, Chuangzhou; Nie, Liangqin; Wu, Xiaokang; Miao, Xiaobo; Chen, Ting; Chen, Liuxi; Zhang, Dongqing; Lin, Quan (Frontiers in Oncology, 2022)
Treatment of ALK-rearranged non-small cell lung cancer (NSCLC) with tyrosine kinase inhibitors (TKIs) is challenged by the almost inevitable emergence of therapeutic resistance. Different profiles of resistance mechanisms have been reported for the currently available ALK TKIs. The ALK C1156Y mutation is reported in 2% of patients with acquired resistance to crizotinib. A rare substitution at the same site, C1156F, remains largely unknown. Existing evidence includes identification of C1156F and G1202R in an alectinib-resistant patient and sensitivity to crizotinib and resistance to later-generation 3ALK inhibitors in preclinical models. In this report, we present two cases in which NSCLC patients acquired the ALK C1156F mutation on crizotinib monotherapy. Both patients were men, and one had been heavily treated with chemotherapeutic regimens before identification of ALK rearrangement, whereas the other received crizotinib as first-line treatment. Genomic profiling of blood biopsies after progression on crizotinib suggested emergence of the ALK C1156F variant. Both patients subsequently received and responded favorably to alectinib, achieving respective progression-free survival of 21 and 15 months as of the latest follow-ups. To the best of our knowledge, this work is the first to provide clinical evidence of resistance to crizotinib and sensitivity to alectinib in NSCLC patients harboring acquired ALK C1156F mutation.